2019
DOI: 10.32861/jssr.52.498.506
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habit and the Health of Undergraduate Students: Evidence from Nigeria

Abstract: The purpose of this study was to examine the relationship between feeding habit and the health of undergraduate students and to also ascertain the level of awareness of students on the nutritional value of food consumed followed by what necessitate their choice of food and how it affect their health. A stratified and simple random sampling method was adopted. Five research questions were raised in the study. Data was collected using a well-structured questionnaire (distributed to 220 students of Landmark Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Unfortunately, many couples particularly in rural communities are illiterates and lack the necessary knowledge to adapt to contemporary family planning methods. This is coupled with the prevailing high poverty rate which places more priority on the need to provide basic food and adequate nutrition for the family ( Arisukwu, Dolapo, Asaleye, Asamu, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many couples particularly in rural communities are illiterates and lack the necessary knowledge to adapt to contemporary family planning methods. This is coupled with the prevailing high poverty rate which places more priority on the need to provide basic food and adequate nutrition for the family ( Arisukwu, Dolapo, Asaleye, Asamu, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The government must drive youth interest and support them with soft loans to take agriculture as a means of earning money. This youth empowerment and support programs by government will promote active youth participation in economic activities and reflect on the feeding habits and health of the rural population ( Arisukwu et al., 2019 ; Asaleye et al., 2018 ).…”
Section: Data Presentation/resultsmentioning
confidence: 99%
“…There is a profound lack of police presence in the rural areas than the urban centers ( Lindström, 2015 ). Youth unemployment, poverty, hunger, poor health and living conditions and ethno-religious challenges are responsible for violence and disenchantment within the rural areas ( Arisukwu, 2017 ; Arisukwu et al, 2019 , 2020 ; Asaju et al, 2014 ). According to National Bureau of Statistics, (2017a , b ), “the labour statistics report of Nigeria in 4 th quarter 2017 has shown that there is 7.9 million Nigerian youths aged 15–34 that are currently unemployed”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors causing the habit of students being late for school include waking up late, no one delivering, deliberately arriving late to school, delaying going to school and waiting for friends, the distance from the schoolhouse that is far away from a leaky motorbike tire. A study said the factors themselves have an important influence in causing the habit of being late for school, including waking up late due to unhealthy body conditions and the desire to leave late for school (Arisukwu et al, 2019). Supported by research which states that students' delay in school is caused by several factors, namely factors that come from themselves (for example, lazy to wake up early, deliberately delaying going to school), family and environmental factors (Das-Friebel et al, 2020).…”
Section: Resultsmentioning
confidence: 99%